1998
DOI: 10.1097/00001756-199804200-00011
|View full text |Cite
|
Sign up to set email alerts
|

Acute plasticity in the human somatosensory cortex following amputation

Abstract: We studied a patient after amputation of an arm and found that in less than 24 h stimuli applied on the ipsilateral face were referred in a precise, topographically organized, modality-specific manner to distinct points on the phantom. Functional magnetic resonance imaging (fMRI) performed one month later showed that brush-evoked activity in the brain demonstrates objective signal changes which correlate with perceptual changes in the phantom hand. This finding in humans corresponds to the observations of imme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
107
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 208 publications
(113 citation statements)
references
References 14 publications
5
107
0
1
Order By: Relevance
“…Cutaneous anaesthesia of the forearm enhances tactile discrimination and the perception of touch in the hand (Bjorkman et al, 2004), presumably because anaesthesia unmasks latent excitatory influences in the thalamus or higher cortical centres. A similar process may account for the rapid development of referred and phantom limb sensations, including pain, following limb amputation (Ramachandran and Hirstein, 1998;Borsook et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous anaesthesia of the forearm enhances tactile discrimination and the perception of touch in the hand (Bjorkman et al, 2004), presumably because anaesthesia unmasks latent excitatory influences in the thalamus or higher cortical centres. A similar process may account for the rapid development of referred and phantom limb sensations, including pain, following limb amputation (Ramachandran and Hirstein, 1998;Borsook et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent PET studies looked at processing during brush-induced allodynia after nerve injury (Witting et al, 2006) and heat allodynia in a patient with neuropathic pain (Casey et al, 2003). Functional magnetic resonance imaging (fMRI) reports include investigations of complex regional pain syndrome (Maihofner and Handwerker, 2005), central pain from syringomyelia (Ducreux et al, 2006), mechanical allodynia in patients with neuropathic pain of central and peripheral origin (Peyron et al, 2004;Hofbauer et al, 2006), and phantom pain (Borsook et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Accurate and detailed somatotopic mapping of the human body surface will improve basic understanding of the somatosensory system, guide neurosurgical planning, and assess plasticity and recovery after brain damage or body injuries (Borsook et al, 1998;Corbetta et al, 2002;Cramer et al, , 2003Cramer and Bastings, 2000;Cramer and Crafton, 2006;Lee et al, 1998Lee et al, , 1999Moore et al, 2000b;Ramachandran, 2005;Ramachandran and Rogers-Ramachandran, 2000;Rijntjes et al, 1997). Studies using fMRI have revealed somatotopic representations of the hand, fingers, wrist, elbow, shoulder, foot, toes, lips, and tongue in human brains (Alkadhi et al, 2002;Beisteiner et al, 2001;Blankenburg et al, 2003;Dechent and Frahm, 2003;Francis et al, 2000;Gelnar et al, 1998;Golaszewski et al, 2006;Hanakawa et al, 2005;Hlustik et al, 2001;Kurth et al, 2000;Lotze et al, 2000;McGlone et al, 2002;Miyamoto et al, 2006;Moore et al, 2000a;Overduin and Servos, 2004;Ruben et al, 2001;Servos et al, 1998;Stippich et al, 1999Stippich et al, , 2004van Westen et al, 2004; also see reviews in Burton, 2002).…”
Section: Introductionmentioning
confidence: 99%